Plynųjų kirtimų poveikis pušynų ekosistemoms ir būdai joms stabilizuoti : mokslinės-praktinės rekomendacijos Impact of clear cuttings on pine wood ecosystems and ways for their stabilization - Juzėnas, Sigitas (Vytautas Magnus University, 2018)
Intensity of forest exploitation increased due to the expanding of use of timber and cutting residues in last years. Changes of the environmental conditions after clear cuttings were very significant, and considerable decline of understory plant and forest entomofauna species was determined. Forest soils were effected by wind and rain in the clear-cutted territories, and fertility of soils depended on the residues in the cutted plots. The presented recommendations are based on the results of the project "Study of impact of clear cuttings on biodiversity dynamics in forest ecosystems", financed by Grant SIT-1/2015 from the Research Council of Lithuania.